A mini-review of heavy metal recycling technologies for municipal solid waste incineration fly ash. Issue 9 (September 2021) - Wang, Huan; Zhu, Fenfen; Liu, Xiaoyan; Han, Meiling; Zhang, Rongyan
This mini-review article summarizes the available technologies for the recycling of heavy metals (HMs) in municipal solid waste incineration (MSWI) fly ash (FA). Recovery technologies included thermal separation (TS), chemical extraction (CE), bioleaching, and electrochemical processes. The reaction conditions of various methods, the efficiency of recovering HMs from MSWI FA and the difficulties and solutions in the process of technical development were studied. Evaluation of each process has also been done to determine the best HM recycling method and future challenges. Results showed that while bioleaching had minimal environmental impact, the process was time-consuming. TS and CE were the most mature technologies, but the former process was not cost-effective. Overall, it has the greatest economic potential to recover metals by CE with scrubber liquid produced by a wet air pollution control system. An electrochemical process or solvent extraction could then be applied to recover HMs from the enriched leachate. Ongoing development of TS and bioleaching technologies could reduce the treatment cost or time.